Everything you need to know about the dangers of computer hacking - Knittel, John, 1973-; Soto, Michael (New York : Rosen Pub. Group, 2000)
Explains what computer hacking is, who does it, and how dangerous it can be.
Includes bibliographical references (p. 61-62) and index.
Keywords: Hackers -- United States -- Juvenile literature; Computer crime -- United States -- Juvenile literature; Computer security -- United States -- Juvenile literature; Internet